Incorporating Khair (IIUM Sejahtera Academic Framework) Holistic Approach in Perioperative Care - Mohamed Zaini, Mohamed Asri Bin; Abdul Ghani, Muhamad Rasydan Bin (International Journal of Human and Health Sciences (IJHHS), 2024)
Introduction: Since its establishment in 2016, SASMEC@IIUM has positioned itself as a leading academic medical centre in Malaysia. The institution integrates the Sejahtera Academic Framework (SAF), which includes KhAIR values (Khalifah, Amanah, Iqra, and Raḥmatan Lil Alamin), into perioperative care. These values are embedded in the perioperative practices of surgeons, anesthetists, and nurses to ensure holistic care for patients undergoing surgery. Methods: The case study identifies the challenges faced in perioperative care, from preoperative patient optimization, intraoperative coordination, to postoperative pain management. These challenges include insufficient patient education, lack of familiarity with new protocols, and inadequate manpower and resources. SASMEC@IIUM implemented several changes aligned with SAF to address these issues. This includes establishing a preoperative anaesthesia clinic for thorough patient assessments, increasing manpower, frequent operational audits, and specialized training for healthcare personnel. Postoperative care was improved through patient-centred pain management and structured rehabilitation plans. Results: The incorporation of SAF and KhAIR values into perioperative care led to significant improvements in patient outcomes. Preoperative optimization became more efficient, with better patient engagement and education. Intraoperatively, the increase in staff and equipment enhanced operational efficiency. Postoperatively, the introduction of Acute Pain Services (APS) rounds and patient-centred pain management resulted in improved pain control, faster recovery, and reduced hospital stays. Conclusion: Integrating Islamic values into perioperative care has revolutionized SASMEC@IIUM's approach to patient management. The focus on holistic, compassionate care, coupled with ethical decision-making, has improved patient satisfaction and outcomes. SASMEC@IIUM's model serves as an exemplary approach for other teaching hospitals aiming for comprehensive, patient-centred care. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S27